2019
DOI: 10.1039/c8sc04935a
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of nanostructuration on the spin crossover transition in crystalline ultrathin films

Abstract: Film thickness and microstructure critically affect the spin crossover transition of a 2D coordination polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 72 publications
(71 reference statements)
5
67
0
Order By: Relevance
“…244 Kitagawa's group procedure for [Fe(py)2Pt(CN)4] films was latter improved by Rubio-Giménez et al by adapting the LbL set-up into a N2-filled glovebox, thus avoiding Fe 2+ oxidation and improving the quality of the films in the ultrathin film range (~1-22 nm). 393 The same research team also extended this procedure to two other 2D Fe II -HCPs [Fe(pym)2Pt(CN)4] and [Fe(isoq)2Pt(CN)4] in a study of the influence of the axial ligand onto the gate-opening solvent uptake. 246 The ALD/MLD technique can also be used in a LbL fashion to build CPs and MOFs in a more aligned way to current CMOS technologies.…”
Section: Sequential Growth By Layer-by-layer/liquid Phase Epitaxymentioning
confidence: 99%
See 1 more Smart Citation
“…244 Kitagawa's group procedure for [Fe(py)2Pt(CN)4] films was latter improved by Rubio-Giménez et al by adapting the LbL set-up into a N2-filled glovebox, thus avoiding Fe 2+ oxidation and improving the quality of the films in the ultrathin film range (~1-22 nm). 393 The same research team also extended this procedure to two other 2D Fe II -HCPs [Fe(pym)2Pt(CN)4] and [Fe(isoq)2Pt(CN)4] in a study of the influence of the axial ligand onto the gate-opening solvent uptake. 246 The ALD/MLD technique can also be used in a LbL fashion to build CPs and MOFs in a more aligned way to current CMOS technologies.…”
Section: Sequential Growth By Layer-by-layer/liquid Phase Epitaxymentioning
confidence: 99%
“…413 Rubio Giménez et al also observed the same effect with nanocrystals of [Fe(py)2Pt(CN)4] (Figure 25b). 393 On the other hand, confinement effects manifested in ultrasmall particles of [Fe(pz)Ni(CN)4] prepared by Bousseksou, Salmon and co-workers. They observed a higher transition temperature in 2-4 nm NPs and even the reappearance of a hysteresis loop.…”
Section: Nanostructuration Effects On the Spin Crossover Transitionmentioning
confidence: 99%
“…The modification on the SCO curve cannot be associated with changes of the crystallinity or a structural phase transition, since a good match was obtained between thin film S3 and reference nanomaterial by X‐ray diffraction (Figure ). Also, no line broadening was observed in the Raman spectra . Presumably, the observed change in SCO behavior results both from the observed particle size reduction in the thin film,[29a] and the interaction at the substrate‐film interface as recently reported by Delgado et al An excessive laser irradiation energy would result in a complete removal of structural water and/or pyrazine molecules, which can even lead to the framework collapse .…”
Section: Resultsmentioning
confidence: 68%
“…The presence of well defined peaks in nanocrystalline thin film confirms that the crystallinity of the deposited sample is not lowered, as noticed by X‐ray diffraction (Figure ). This result is of the utmost importance compared to classic sublimation methods of SCO complexes, which usually lead to a decrease or even a complete disappearance of the crystallinity of deposited materials . Remarkable differences in band intensities assigned to pyrazine modes at ca.…”
Section: Resultsmentioning
confidence: 98%
“…The surface/interface energy can be therefore viewed as a key parameter, which governs the SCO properties at the nanoscale . Understanding surface/interface phenomena is not only important to elucidate nanoscale SCO behaviors but also opens up possibilities for engineering these nanomaterials . However, thin films and nanostructures usually have nonuniform properties due to defects, grain boundaries, strain distributions, and so forth.…”
Section: Comparison Of Reported Elastic Moduli Ofmentioning
confidence: 99%